Differential Expression Profiles and Function Predictions for tRFs & tiRNAs in Skin Injury Induced by Ultraviolet Irradiation - Fang, Yuan; Liu, Yang; Yan, Yu; Shen, Yiyu; Li, Zenan; Li, Xu; Zhang, Yufang; Xue, Zhigang; Peng, Cong; Chen, Xiang; Cao, Ke; Zhou, Jianda (Frontiers in Cell and Developmental Biology, 2021)
Ultraviolet (UV) radiation is a major environmental factor contributing skin damage. As UV exposure is inevitable, it is necessary to pay attention to the underlying molecular mechanisms of UV-induced skin damage to develop effective therapies. tRNA-derived stress-induced RNAs (tiRNAs) and tRNA-derived fragments (tRFs) are tRNA-derived small RNAs (tsRNAs) that are a novel class of short, non-coding RNAs. However, the functions behind tRFs & tiRNAs in UV-induced skin injury are not yet clear. Firstly, the animal model of ultraviolet irradiation induced skin damage was established. Then the skin samples were preserved for the follow-up experiment. Sequencing was used to screen expression profiles and predict target genes. Compared with normal skin, a total of 31 differentially expressed tRFs & tiRNAs were screened. Among these, 10 tRFs & tiRNAs were shown to be significantly different in expression levels, where there were 4 up-regulated and 6 down-regulated target genes. Bioinformatics analyses revealed potential up-regulated tsRNAs (tRF-Val-AAC-012, tRF-Pro-AGG-012, tRF-Val-CAC-018, tRF-Val-AAC-031) and down-regulated tsRNAs (tRF-Arg-CCT-002, tRF-Trp-TCA-001, tiRNA-Ser-GCT-001, tRF-Gly-CCC-019, tRF-Ala-TGC-001, tRF-Ala-TGC-002). In summary, it was speculated that tRF-Gly-CCC-019 plays an important role in acute skin injury induced by UVB radiation by regulating the ras-related C3 botulinum toxin substrate 1 (Rac1) gene in the WNT signaling pathway. This study provides new insights into the mechanisms and therapeutic targets of UV-induced skin injury.